2019
DOI: 10.1172/jci.insight.126925
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale lipidomics identifies associations between plasma sphingolipids and T2DM incidence

Abstract: BACKGROUND. Sphingolipids (SPs) are ubiquitous, structurally diverse molecules that include ceramides, sphingomyelins (SMs), and sphingosines. They are involved in various pathologies, including obesity and type 2 diabetes mellitus (T2DM). Therefore, it is likely that perturbations in plasma concentrations of SPs are associated with disease. Identifying these associations may reveal useful biomarkers or provide insight into disease processes. METHODS. We performed a lipidomics evaluation of molecularly distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
113
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 45 publications
14
113
1
1
Order By: Relevance
“…1A) and significantly higher in females than in males. This confirms data from two recent epidemiologic studies, which also report gender-specific difference in d18:2-based SLs (16,17).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…1A) and significantly higher in females than in males. This confirms data from two recent epidemiologic studies, which also report gender-specific difference in d18:2-based SLs (16,17).…”
Section: Discussionsupporting
confidence: 90%
“…Little is known about the function of d18:2-based SLs. Previously, plasma levels of d18:2 SLs were inversely associated with the incidence of cardiovascular events (8), the body mass index, and the HOMA (homeostatic model assessment) index (16). It serves as a backbone for complex sphingolipids (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Dots and lines in red represent significant association biomarkers for various conditions including cancer, neurodegenerative, metabolic, autoimmune. and vascular diseases [25,[44][45][46][47][48][49][50]. In the current study, we observed alterations of plasma sphingosine-1-phosphate (S1P) species in a cohort of aged cognitively normal subjects as well as people with vascular cognitive impairment (VCI) and Alzheimer's disease (AD).…”
Section: Discussionmentioning
confidence: 83%
“…We previously found plasma levels of sphingadienine inversely associated with the risk of major cardiovascular events during a follow-up of 8 years in patients who underwent coronary angiography (44). Most recently, plasma levels of sphingadienine-based lipids were found inversely associated with BMI and the HOMA insulin resistance index (47). Sphingadienine is likely generated by the desaturation of sphingosine through an as yet unknown enzyme.…”
Section: Discussionmentioning
confidence: 97%